Compliance with Drug Use in Hypertension Patients Reviewed from Age Factors, Education Level and Length of Hypertension Suffering - Susanti, Ratna Eka; Mawaddah, Nurul (PT Saintek Medika Nusantara, 2023)
Compliance with hypertension treatment is important because hypertension is an incurable disease but must always be controlled or managed so that complications that can lead to death do not occur. This study is an analytical observational study with a cross-sectional study design. The researcher used a cross-sectional design because in this study, observation or measurement of variables was carried out at a predetermined time with a population of 757 respondents. The sampling used in this study was purposive sampling with a sample size of 30 respondents. From the results of this study, it can be concluded that the last level of education factor with a sig value of 0.000), f age factor with a sig value of 0.016, duration of hypertension with a sig value = 0.000, has a relationship with compliance in undergoing hypertension treatment. Compliance is a form of behavior that arises as a result of interaction between health workers and patients so that patients understand the plan with all its consequences and agree to the plan and carry it out. Hypertension treatment is a long-term treatment, maybe even lifelong, treatment using standard triple therapy (STT) is the basis for hypertension treatment. The goal of hypertension treatment is to reduce morbidity rates so that efforts to find antihypertensive drugs that meet expectations continue to be developed.